COVID‐19 vaccine in patients with Dravet syndrome: Observations and real‐world experiences. Issue 7 (20th April 2022) - Hood, Veronica; Berg, Anne T.; Knupp, Kelly G.; Koh, Sookyong; Laux, Linda; Meskis, Mary Anne; Zulfiqar‐Ali, Quratulain; Perry, M. Scott; Scheffer, Ingrid E.; Sullivan, Joseph; Wirrell, Elaine; Andrade, Danielle M.
Abstract: Objective: Vaccination against the SARS‐CoV‐2 virus is a primary tool to combat the COVID‐19 pandemic. However, vaccination is a common seizure trigger in individuals with Dravet syndrome (DS). Information surrounding COVID‐19 vaccine side effects in patients with DS would aid caregivers and providers in decisions for and management of COVID‐19 vaccination. Methods: A survey was emailed to the Dravet Syndrome Foundation's Family Network and posted to the Dravet Parent & Caregiver Support Group on Facebook between May and August 2021. Deidentified information obtained included demographics and vaccination status for individuals with DS. Vaccine type, side effects, preventative measures, and changes in seizure activity following COVID‐19 vaccination were recorded. For unvaccinated individuals, caregivers were asked about intent to vaccinate and reasons for their decision. Results: Of 278 survey responses, 120 represented vaccinated individuals with DS (median age = 19.5 years), with 50% reporting no side effects from COVID‐19 vaccination. Increased seizures following COVID‐19 vaccination were reported in 16 individuals, but none had status epilepticus. Of the 158 individuals who had not received a COVID‐19 vaccination, 37 were older than 12 years (i.e., eligible at time of study), and only six of these caregivers indicated intent to seek vaccination. The remaining 121 responses were caregivers to children younger than 12 years, 60 of whom indicated they would not seek COVID‐19 vaccination when their child with DS became eligible. Reasons for vaccine hesitancy were fear of increased seizure activity and concerns about vaccine safety. Significance: These results indicate COVID‐19 vaccination is well tolerated by individuals with DS. One main reason for vaccine hesitancy was fear of increased seizure activity, which occurred in only 13% of vaccinated individuals, and none had status epilepticus. This study provides critical and reassuring insights for caregivers and health care providers making decisions about the safety of COVID‐19 vaccinations for individuals with DS.